2007
DOI: 10.47102/annals-acadmedsg.v36n11p937
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the SMN1 and NAIP Genes in Iranian Patients with Spinal Muscular Atrophy

Abstract: Introduction: Childhood-onset proximal spinal muscular atrophies (SMAs) are an autosomal recessive, clinically heterogeneous group of neuropathies characterised by the selective degeneration of anterior horn cells. SMA has an estimated incidence of 1 in 10,000 live births. The causative genes are survival motor neuron (SMN) gene and neuronal apoptosis inhibitory protein (NAIP) gene. Deletions of the telomeric copy of SMN gene (SMN1) have been reported in 88.5% to 95% of SMA cases, whereas the deletion rate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…The rate of consanguineous marriages in our study was 23.5%; an SMA study from Iran reported 97% consanguinity, 24 68% consanguinity was reported in a study from Turkey, 18 a prenatal diagnosis study from Turkey reported consanguinity in 21 of 63 families 25 because autosomal recessive diseases are a common result of consanguinity. The rate of consanguinity in our study is at a lower rate for our country.…”
Section: Discussionsupporting
confidence: 41%
“…The rate of consanguineous marriages in our study was 23.5%; an SMA study from Iran reported 97% consanguinity, 24 68% consanguinity was reported in a study from Turkey, 18 a prenatal diagnosis study from Turkey reported consanguinity in 21 of 63 families 25 because autosomal recessive diseases are a common result of consanguinity. The rate of consanguinity in our study is at a lower rate for our country.…”
Section: Discussionsupporting
confidence: 41%